Pengaruh Model Pembelajaran Project Based Learning dengan Menggunakan Mind Mapping terhadap Hasil Belajar Siswa di kelas Vlll SMP Negeri 5 Bolano Lambunu - Maharani, Sri; Lilies, Lilies; Rauf, Abd; Bustamin, Bustamin; Ashari, Abd; Bialangi, Mursito S (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of the Project Based Learning learning model using Mind Mapping on student learning outcomes in class VIII of SMP Negeri 5 Bolano Lambunu. This research method is a quasi-experiment (Quasi Experiment) with a Non-equivalent (Pretest and Posttest) Control Group Design. The sample of this study was 34 students, consisting of 17 students in the experimental class who used the Project Based Learning learning model using Mind Mapping and 17 students in the control class who used the conventional learning model. Data collection was carried out by conducting observations, interviews, and tests. Data analysis used prerequisite tests, namely, normality tests and homogeneity tests and hypothesis testing using the Independent Sample t-test and N-gain tests. The results of the study showed that (1) there was an effect of using the Project Based Learning learning model using Mapping on student learning outcomes. This is evidenced by a significant increase in student learning outcomes in the experimental class, with an average posttest score reaching 73.23, while the control class was only 64.70. The t-test shows a p value < 0.05, which means that the implementation of the Project Based Learning model using Mapping has a positive effect on student learning outcomes. (2) N-gain analysis shows that the experimental class has an average N-gain score of 0.65 (65%), which is included in the fairly effective category, while the control class is only 0.51 (51%), which indicates a less effective category. Thus, it can be concluded that the Project Based Learning learning model using Mind Mapping is effective and can affect student learning outcomes in the science subject of class VIII-B SMP Negeri 5 Bolano Lambunu.